Presumptive Zoonotic Kerion by Nannizzia gypsea: Case Report - Cruciani, Deborah; Papini, Manuela; Broccatelli, Sayra; Agnetti, Francesco; Spina, Sara; Natalini, Ylenia; Crotti, Silvia (Frontiers in Veterinary Science, 2021)
Nannizzia (N.) gypsea belongs to geophilic dermatophytes, fungi involved in keratin degradation in the soil however also found in dogs and cats. Transmission to humans can occur directly by contact with soil, but indirect transmission via domestic animals is reported too. The exact source of the infection is usually difficult to assess and in most cases only hypothesized and rarely investigated. This case report describes a kerion caused by N. gypsea in a 2-year-old boy, where the contagion was probably secondary to domestic healthy carrier dogs. A “One-Health” approach involving human dermatologists and veterinarians, combined with the use of conventional and molecular based techniques allowed tracing of the epidemiological chain and managing of not only the treatment, but also the prevention of a recurrence. The child’s lesion began to regress after about 8 weeks of treatment with both systemic and topical therapy while the dogs were given chlorhexidine and miconazole baths. No recurrences nor new infections occurred demonstrated the effectiveness of the strategies used.